Great events that changed the world - Delf, Brian; Platt, Richard (New York : DK Pub., 1997)
Text and illustrations present an overview of such important historical topics as the Roman Empire, the First Crusade, the fall of the Aztecs, the Moghul Empire, and the French Revolution.
Originally published: London : Dorling Kindersley, 1997.
Includes index.
Keywords: World history -- Juvenile literature; World history -- Pictorial works. -- Pictorial works; World history